Enhancing business-to-business relationship through value co-creation in traditional business sector: A case of building services engineering - Seppä, Marja (My University, 2014)
This study discusses the significance of having service as a business logic, and more specifically, how value co-creation can be seen as an enhancing phenomenon to business-to-business relationships in traditional business sector. The purpose of this study is to investigate how value cocreation can enhance a business-to-business relationship in the heating, ventilation and airconditioning (HVAC) industry of building services engineering, through three sub-objectives: to identify what is value in the industry, how value is co-created in the industry, and what is value in a business-to-business relationship in the industry. The theoretical part this study consists of academic knowledge and literature related to the concepts of value, value co-creation and business-to-business relationships. In order to research value co-creation and business-to-business relationships in HVAC industry of building services engineering both, metaphorical and conceptual thinking of service dominant (S-D) logic and more managerial approach of service logic (SL), contributed to the theoretical part of the study. The empirical research conducted for this study is based on seven semi-structured interviews, which constituted the holistic, qualitative single case study method chosen for the research. The data was collected in September 2014 from CEOs, managers and owners representing six building services engineering firms. The interviews were analysed with the help of transcriptions, role-ordered matrices and thematic networks. The findings of this study indicate that value in HVAC industry consists of client expertise and supplier expertise. The result of applying client expertise and supplier expertise to the business-to- business relationship is characterized as value-in-reputation, when continuity, interaction, learning and rapport of the business relationship are ensured. As a result, value co-creation in the industry consists of mutual and separate elements, which the client and the supplier apply in the process, in addition to proactive interaction. The findings of this study, together with the final framework, enhance the understanding of the connection existing between value co-creation and business-to-business relationship. The findings suggest that value in the HVAC industry is characterized by both value-in-use and value-inreputation. Value-in-reputation enhances the formation of value-in-use, and consequently, value cocreation enhances the business-to-business relationship. This study thus contributes to the existing knowledge on the concepts of value and value co-creation in business-to-business relationships.